A Coupled Thermo-Hydromechanical Model of Soil Slope in Seasonally Frozen Regions under Freeze-Thaw Action - Yongxiang Zhan; Zheng Lu; Hailin Yao; Shaohua Xian (Advances in Civil Engineering)
Soil slope diseases in seasonally frozen regions are mostly related to water migration and frost heave deformation of the soil. Based on the partial differential equation defined using the COMSOL Multiphysics software, a thermo-hydromechanical coupling model considering water migration, ice-water phase change, ice impedance, and frost heave is constructed, and the variations in the temperature field, migration of liquid water, accumulation of solid ice, and deformation of frost heave in frozen soil slopes are analysed. The results show that the ambient temperature has a significant effect on the temperature and moisture field of the slope in the shallow area. In addition, the degree of influence gradually weakens from the outside to the inside of the slope, and the number of freeze-thaw cycles in deep soil is less than that in shallow soil. During the freezing period, water in the unfrozen area rapidly migrates to the frozen area, and the total moisture content abruptly changes at the vicinity of the freezing front. The maximum frozen depth is the largest at the slope top and the smallest at the slope foot. During the melting period, water is enriched at the melting front with the frozen layer melting; the slope is prone to shallow instability at this stage. The melting of the frozen layer is bidirectional, so the duration of slope melting is shorter than that of the freezing process. The slope displacement is closely related to the change in temperature—a relation that is in agreement with the phenomenon of thermal expansion and contraction in unfrozen areas and reflects the phenomenon of frost heave and thaw settlement in frozen areas.